The Influence of Organizational Commitment, Transformational Leadership, and Compensation on Turnover Intention Using Job Satisfaction as a Mediator at One of State-Owned Banks in Indonesia - Prasetyaningtyas, Sekar Wulan; Alkautsar, Isminanda; Riomudita, Riomudita; Steven, Steven (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines the impact of organizational commitment, transformational leadership, and compensation on turnover intention, with job satisfaction as a mediator. Conducted among employees of a state-owned bank in Indonesia, the research utilized Smart PLS and structural equation modeling for data analysis. The results indicate that organizational commitment, transformational leadership, and compensation all have significant negative direct effects on turnover intention. Furthermore, job satisfaction is found to be a strong mediator, enhancing the impact of each variable on reducing turnover intention. The study emphasizes practical strategies for reducing turnover and enhancing retention, recommending competitive compensation packages and leadership development focused on transformational qualities. These measures can foster employee engagement and lower turnover rates, improving organizational performance. This research contributes to understanding these dynamics in the Indonesian banking sector, addressing a gap in literature compared to Western studies. It underscores the importance of retaining skilled employees in Indonesia's competitive economic landscape, offering actionable insights for bank management to enhance employee engagement and organizational effectiveness.